2024
DOI: 10.1088/1361-6501/ad2667
|View full text |Cite
|
Sign up to set email alerts
|

A zero-shot fault attribute transfer learning method for compound fault diagnosis of power circuit breakers

Qiuyu Yang,
Yuyi Lin,
Jiangjun Ruan

Abstract: Diagnosis of compound mechanical faults for power circuit breakers (CBs) is a challenging task. In traditional fault diagnosis methods, however, all fault types need to be collected in advance for the training of diagnosis model. Such processes have poor generalization capabilities for industrial scenarios with no or few data when faced with new faults. In this study, we propose a novel zero-shot learning method named DSR-AL to address this problem. An unsupervised neural network, namely, depthwise separable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Since the optimization algorithm has randomness, the result of each iteration will be different, so the optimal parameter combination [α, K] is obtained by averaging the results after 20 times of optimization in this paper. Among them, the value range of penalty factor α is [0,3000], the value range of decomposition modulus K is [3,8] and is an integer, and the maximum number of iterations is 20. The optimization results are shown in table 3.…”
Section: Parameter Optimization Based On Ssa-vmdmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the optimization algorithm has randomness, the result of each iteration will be different, so the optimal parameter combination [α, K] is obtained by averaging the results after 20 times of optimization in this paper. Among them, the value range of penalty factor α is [0,3000], the value range of decomposition modulus K is [3,8] and is an integer, and the maximum number of iterations is 20. The optimization results are shown in table 3.…”
Section: Parameter Optimization Based On Ssa-vmdmentioning
confidence: 99%
“…Therefore, implementing an intelligent evaluation and detection of CB functioning state is important from a theoretical and engineering standpoint. A multinational survey [2][3][4] found that mechanical failure accounts for approximately 59.9% of CB failures, with operating mechanism failure being the primary cause of CB mechanical failure.…”
Section: Introductionmentioning
confidence: 99%